Chrysomya albiceps, a new agent of secondary skin myiasis in sheep in Brazil - Oliveira, Carlos Marcos B. de (Pesquisa Agropecuaria Brasileira, 2014)
A register, for the first time in Brazil, of the occurrence of secondary skin myiasis caused by Chrysomya albiceps in sheep.